DOCHODY WŁASNE JEDNOSTEK SAMORZĄDU TERYTORIALNEGO W POLSCE - Kotlińska, Janina (Wydział Prawa i Administracji UAM, 2009)
The classification and definition of the local government revenue differs when it comes to law and law literature. One of the categories found within both is a self-generated revenue. Its numerous definitions, however, often contradict one another, and consequently there are different opinions regarding the depth of financial independence at particular levels of local government. The purpose of the study was to explain the meaning of self-generated revenue of a local government as well as indicate its sources, structures and the controversies involved. Furthermore, the study aimed to explain how this particular type of revenue fits into the income structure of the local government and how independent the local government in Poland is. The answer to this question may to be achieved by detailed analyses of the attributes of the local government’s self-generated income and empirical data reflecting the local government’s income structure between 1999 and 2007.
SELF-GENERATED REVENUES OF LOCAL GOVERNMENTS IN POLAND